HPLC Standardization of The Methanolic Extract of Acrocarpus fraxinifolius leaves based on Gallic acid Content - Heba A.S. El-Nashar; Omayma A. Eldahshan; Abdel Nasser B. Singab (Ain Shams University, 2017)
High-Performance Liquid Chromatography (HPLC) was developed for the standardization and quantification of gallic acid in the methanolic extract of Acrocarpus fraxinifolius Weight & Arn leaves. Linearity was observed in the range of 0.4-2 mg/mL with a correlation coefficient (r2) of 0.9978. The limit of detection (LOD) and limit of quantification (LOQ) were 0.0054 mg/mL and 0.0163 mg/mL, respectively indicating the sensitivity of the applied method. Recovery values of 100.377 % indicate the best accuracy of the method. Gallic acid content was quantified as 168.75 ± 1.05 mg/g methanolic extract. This developed method was simple, accurate and precise to be used as a reference standard method for determination of gallic acid content in the plant extract